2014
DOI: 10.1080/17441692.2014.981832
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with HIV testing among male motorbike taxi drivers in urban Vietnam

Abstract: Using the Attitude-Skills-Knowledge (ASK) model, this study examined the prevalence of, and factors associated with, human immunodeficiency virus (HIV) testing among male motorbike taxi drivers (MMTDs). In a cross-sectional design, using quantitative approaches, 291 MMTDs were recruited from 135 sites across 13 districts in Hanoi, Vietnam, for a face-to-face interview. Applying the ASK model modified as a central theory, logistic regression was used to identify determinants of HIV testing. Although many MMTDs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…This is similar to other studies where HIV testing increased with higher number of past year sex partners among male motorbike taxi drivers (92.1% were heterosexual) in urban Vietnam [36] and among the general heterosexual male population in Italy [16]. For having engaged in anal sex, our result showed an almost two-fold significant association with HIV/STI testing although this was not observed in heterosexual men who attended the STI clinics in China [20].…”
Section: Discussionsupporting
confidence: 91%
“…This is similar to other studies where HIV testing increased with higher number of past year sex partners among male motorbike taxi drivers (92.1% were heterosexual) in urban Vietnam [36] and among the general heterosexual male population in Italy [16]. For having engaged in anal sex, our result showed an almost two-fold significant association with HIV/STI testing although this was not observed in heterosexual men who attended the STI clinics in China [20].…”
Section: Discussionsupporting
confidence: 91%
“…However, Quynh et al found that most of them rented accommodation with very poor quality and sanitation standards [24]. The extant literature on the relationship between health and internal labor migration in Vietnam has primarily examined a number of prevalent health risks, such as HIV/AIDS vulnerability and transmission [25,26,27], reproductive tract infection among female migrants [28,29], excessive alcohol consumption among male street laborers [30], sexual practices and sexually transmissible infections among migrant sex workers [31,32], or malaria incidence in the at-risk migrant population [33]. Given continuing migration and uneven economic integration and growth, ensuring the detection of health issues and timely provision of health services in migrant workers is crucial to national health equity [34].…”
Section: Introductionmentioning
confidence: 99%
“…HIV testing has been considered as an important service in intervention strategy against HIV/AIDS, but it has been neglected among many high-risk groups in Vietnam. Using the Attitude – Skills – Knowledge (ASK) model, Huy, Khuyen, and Ha (2014) examined factors associated with HIV testing among male motorbike taxi drivers. The study showed that only a few men among the study subjects had been tested for HIV during the past 12 months.…”
mentioning
confidence: 99%